Cholinesterase in different types of the muscle tissue during the early postmortem period for diagnosis of death coming (Bangladesh Journal of Medical Science, 2021)
The purpose of the research: consisted in study of postmortem regularities in the content of cholinesterasein different types of muscle tissue (MT) for improving accuracy of determination of the prescriptionof death coming PDC.Materials and methods: The activity/level of cholinesterase was determinedin homogenates of the myocardial (MMH), oesophageal (OMH), diaphragm (DMH) and intercostalmuscles (IMH)within the early PMP (3-13 hours after the coming of death) on 30 human corpses. MTwas sampled in conditions of postmortem biopsy with use of special instruments; MT homogenateswere prepared following the standard technique with subsequent determination of cholinesterase content in MT homogenates.Results and discussion: The analysis of postmortem changes in the content ofcholinesterase in MT depending upon PDC revealed that after 3 hours from the moment of death comingits highest content was in muscles of the oesophagus, the least one being in MT of the intercostal muscles(respectively, (2,717.1±37.1) and (883.5±6.2) U/g, р